Peran Pemerintah Desa Dalam Upaya Peningkatan PAD Desa Melalui Peningkatan Mutu UMKM Desa Pulau Harapan Kecamatan Sembawa Kabupaten Banyuasin - Arista, Windi; Sugianto, Bambang; Yuliza, Yuliza; Merita, Enni (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This study examines the strategic role of the Pulau Harapan Village Government in increasing Village Original Income (PAD) through improving the quality of Micro, Small, and Medium Enterprises (MSMEs) with the aim of optimizing the role of village officials in increasing Village Original Income (PADes). MSMEs are an economic sector that plays a vital role in creating jobs, increasing community income, and driving village economic growth. This study uses descriptive qualitative methods through interviews, field observations, and documentation studies. The results show that the village government has implemented various programs such as capacity training, licensing facilitation, capital assistance, increased market access, and MSME digitalization. However, several obstacles such as budget limitations, lack of innovation among MSME actors, and minimal digital literacy are the main challenges. The results of the activities are expected to become a model of sustainable empowerment in increasing PADes based on local potential. This article provides recommendations for strengthening the village MSME ecosystem as a strategy for increasing PAD.